Composition, Stratigraphy, and Geological History of the Noachian Basement Surrounding the Isidis Impact Basin. Issue 7 (7th July 2020) - Scheller, Eva L.; Ehlmann, Bethany L.
Abstract: The western part of the Isidis basin structure hosts a well‐characterized Early Noachian to Amazonian stratigraphy. The Noachian Basement comprises its oldest exposed rocks (Early to Mid‐Noachian) and was previously considered a single low‐Ca pyroxenes (LCP)‐ and Fe/Mg‐smectite‐bearing unit. Here, we divide the Noachian Basement Group into five distinct geological units (Stratified Basement Unit, Blue Fractured Unit, Mixed Lithology Plains Unit, LCP‐bearing Plateaus Unit, and Fe/Mg‐smectite‐bearing Mounds Unit), two geomorphological features (megabreccia and ridges), and a mineral deposit (kaolinite‐bearing bright materials), based on geomorphology, spectral characteristics, and stratigraphic relationships. Megabreccia contain four different pre‐Isidis lithologies, possibly including deeper crust or mantle materials, formed through mass wasting associated with transient crater collapse during Isidis basin formation. The Fe/Mg‐smectite‐bearing Stratified Basement Unit and LCP‐bearing Blue Fractured Unit likewise represent pre‐Isidis units within the Noachian Basement Group. Multiple Fe/Mg‐smectite‐bearing geological units with different stratigraphic positions and younger kaolinite‐bearing bright materials indicate several aqueous alteration episodes of different ages and styles. Units with slight changes in pyroxene spectral properties suggest a transition from low‐Ca pyroxene‐containing materials to those with higher proportions of pyroxenes higher in Ca and/or glass that could be related to different impact and/or igneous processes, or provenance. This long history of Noachian and potentially Pre‐Noachian geological processes, including impact basin formation, aqueous alteration, and multiple igneous and sedimentary petrogeneses, records changing ancient Mars environmental conditions. All units defined by this study are available 20 km outside of Jezero crater for in situ analysis and sampling during a potential extended mission scenario for the Mars 2020 rover. Plain Language Summary: The Isidis basin's Noachian Basement Group is a collection of geological materials that are among the oldest rocks exposed on the Martian surface (>3.8 billion years old). We have characterized their spectral signatures and appearances using instruments on the Mars Reconnaissance Orbiter. The Noachian Basement Group contains eight different geological categories of rocks formed at different times and by different processes. One of these categories is megabreccia, which are blocks of rocks created when a meteorite impact formed the 1, 900‐km Isidis impact basin. The megabreccia contain materials from deep within Mars and likely formed during enormous landslides after the impact. The spectral properties of the megabreccia reveal that they contain four different types of rock that must have originated before the Isidis impact basin formed. Through investigations of the three‐dimensional relationships between our eight categories of geological materials, we observe that they record multiple distinct water‐rich environments, multiple igneous processes, and giant impact processes, during an ancient time period that we know little about. Furthermore, all eight different rock categories can be studied and sampled with the next Mars rover, set to launch in 2020, which will answer outstanding questions about the climate, astrobiology, and geological processes on early Mars. Key Points: The Noachian Basement Group contains a newly defined stratigraphy of five geological units and three geomorphological or mineralogical features Isidis‐related megabreccia likely formed through mass wasting during transient crater collapse and record four distinct pre‐Isidis lithologies A M2020 extended mission would provide deep crust, impact melt, and hydrated lithologies of distinct Pre‐Noachian or Early Noachian ages